Drug-drug interactions with direct oral anticoagulants associated with adverse events in the real world: A systematic review. Issue 194 (October 2020) - Li, Allen; Li, Ming K.; Crowther, Mark; Vazquez, Sara R.
Abstract: Background: Direct oral anticoagulants (DOACs) have emerged as safe and effective alternatives to Vitamin-K antagonists for treatment and prevention of arterial and venous thrombosis. Due to their novelty, pharmacokinetic DOAC drug-drug interactions (DDIs) that result in clinical adverse events have not been well-documented. Objective: This study aims to systematically review reported pharmacokinetic DDIs resulting in clinical adverse events through documented observational evidence to better inform clinicians in clinical practice. Methods: A comprehensive literature review of EMBASE, MEDLINE, and Ovid HealthStar was conducted through March 10th, 2020. Two independent reviewers screened and extracted data from eligible articles according to pre-established inclusion and exclusion criteria. Articles reporting bleeding or thrombotic outcomes in non-controlled (observational) settings resulting from suggested pharmacokinetic DOAC DDIs were included. Results: A total of 5567 citations were reviewed, of which 24 were included following data extraction. The majority were case reports ( n  = 21) documenting a single adverse event resulting from a suspected DOAC DDI, while the remaining papers were a case series ( n  = 1) and cohort studies ( n  = 2). The most commonly reported interacting drugs were amiodarone and ritonavir (bleeding), and phenobarbital, phenytoin, and carbamazepine (thrombosis). Bleeding events more often resulted from a combined mechanism (P-glycoprotein AND CYP3A4 inhibition), whereas thrombotic events resulted from either combined OR single P-glycoprotein/CYP3A4 induction. Conclusion: Current literature evaluating the real-world risk of DOAC DDIs is limited to few case reports and retrospective observational analyses. Clinicians are encouraged to continue to report suspected drug interactions resulting in adverse events. Highlights: Patients on direct oral anticoagulants (DOACs) can encounter drug interactions. Drug interactions can alter the amount of DOAC in a patient's system. Research on DOAC interactions is currently limited and larger studies are required. Health providers should continue to be cautious with potential DOAC interactions.